2022
DOI: 10.25259/sni_494_2022
|View full text |Cite
|
Sign up to set email alerts
|

In vivo goat brain model for neurosurgical training

Abstract: Background: Novice neurosurgeons require neurosurgical technique training, but the current method is demanding and time consuming. Therefore, it is crucial to perform training using an appropriate and informative method. In this report, we describe our attempts to provide training in neurosurgical techniques using goat in vivo brain model and to demonstrate the effectiveness of this model. Methods: Under general anesthesia, the surgery was performed on a male goat in the prone position. A midline liner ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 10 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…We recently reported the usefulness of in vivo goat brain model in neurosurgical training. [ 11 ] The goat brain has a human-like brain texture and anatomical structures such as blood vessels and nerves that are similar to those of humans. Since in vivo goat brain model is not a cadaveric brain, it allows for realistic training such as a hemostatic manipulation in a pulsating brain and blood vessel.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We recently reported the usefulness of in vivo goat brain model in neurosurgical training. [ 11 ] The goat brain has a human-like brain texture and anatomical structures such as blood vessels and nerves that are similar to those of humans. Since in vivo goat brain model is not a cadaveric brain, it allows for realistic training such as a hemostatic manipulation in a pulsating brain and blood vessel.…”
Section: Discussionmentioning
confidence: 99%
“…Since in vivo goat brain model is not a cadaveric brain, it allows for realistic training such as a hemostatic manipulation in a pulsating brain and blood vessel. [ 11 ] In addition, it was indicated that the interhemispheric and the retrosigmoid approaches are possible. [ 11 ] The present study used an in vivo goat model and indicated the usefulness of this model not only for neurosurgical technique training but also for neuroendoscopic research.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations